The Existence of Madura Grocery Stalls in the Siege of Modern Franchise Minimarkets - Eko Setiawan; Ismi Lufina (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
Madura grocery stalls are found in many corners of major cities in Indonesia. In general, it only sells a variety of daily necessities at relatively affordable prices but has unique operating hours of 24 hours. So that it can compete in the midst of the siege of modern franchises, the turnover obtained can be said to be quite fantastic. This type of research is a case study (case study) part of a qualitative method that aims to understand a phenomenon by providing a complete picture, views, and behavior of informants in detail based on natural situations. Data collection methods use observation, unstructured interviews, and documentation. Data analysis using interactive models, through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the existence of Madurese grocery stalls could grow rapidly and dare to challenge well-known franchise minimarket networks because they applied kinship-based business patterns. They build social cohesion based on mechanical solidarity, describing how strong the cohesiveness or attachment of society is.